Efek Antibakteri dari Kombinasi Minyak Atsiri Masoyi dan Kayu Manis - Rollando, Rollando; Sitepu, Rehmadanta (Jurnal Kefarmasian Indonesia, 2018)
Essential oils had been used as antibacterial, antifungal, antiviral, antioxidant and insecticidal in medicine and industry. Increasing the usage of essential oils as an alternative medication also lead more research of essential oils in vivo and in vitro. Cinnamon with cynamaldehide as a main active substance and masoyi with massoia lacton as a main active substance have antibacterial activity.This study aimed to determine the activity of masoyi and cinnamon essentials oils combinationin E.coli, S.aureus, and P.aeruginosabacteria. The research encompasses antibacterial activity screening and antibacterial evaluation. The aims of essential oil activity screening using Kirby-Bauer method is to find the optimum concentration of masoyi and cinnamon essentials oils combination. Determination of MIC50, MIC90, and MBC concentration is using microdilution method. Kirby-Bauer test results showed the highest inhibitory concentration that had bactericidal effect to E.coli, S.aureus, and P.aeruginosa were the combination of